Achieving battery-level energy density by constructing aqueous carbonaceous supercapacitors with hierarchical porous N-rich carbon materials12. Issue 21 (7th June 2015) - Yang, Mei; Zhong, Yiren; Bao, Jie; Zhou, Xianlong; Wei, Jinping; Zhou, Zhen
<x xml:space="preserve">Abstract</x> 3D hierarchical porous N-rich graphitic carbon materials were prepared and further used for symmetric aqueous supercapacitors with battery-level energy density while retaining capacitor-type power density and cycling stability.